ANALISIS ELEMEN VERTIKAL PADA BANGUNAN SEKOLAH KHUSUS OLAHAGA CIBUBUR MENGGUNAKAN METODE RESPONSE SPECTRUME - Amini, Aina Riva; Darmiyanti, Lydia; Rodji, Achmad Pahrul (Jurnal Anggapa, 2025)
Earthquakes, caused by the movement of active tectonic plates, pose a real risk to infrastructure in Indonesia, especially in rapidly developing urban areas with high-rise building construction. Although the Cibubur area has a low earthquake risk based on SNI 1726:2019, earthquake impact analysis in construction design remains crucial. Many building collapses due to earthquakes are often caused by a lack of understanding of earthquake resistance principles in their design and implementation. Thus, in-depth structural analysis is crucial to ensure the building can withstand various types of loads, including dynamic loads due to earthquakes. This study aims to analyze the vertical components of the Cibubur Special Sports School Building using the Response Spectrum Analysis method. The specific objectives are to measure the values ??of shear forces and displacements in columns due to earthquakes, as well as the comparison of column reinforcement. Data were collected through literature review and technical data collection such as shop drawings. The analysis conducted using ETABS V.18.1.1 software showed that the highest shear forces in the second-floor columns reached 1615.402 kN (X direction) and 1482.65 kN (Y direction). The current displacement caused by the earthquake is 309,071 mm (X-direction) and 285,402 mm (Y-direction). The K1 column reinforcement ratio of 2.47% is within the limits permitted by SNI 2847-2019. This study is expected to provide insight into the structural response to earthquake loads, assist in determining the feasibility and safety of buildings, and prepare for reinforcement needs.